A temperature-sensitive composite hydrogel and a preparation method and application thereof
Patent Information
- Application Number
- CN202610975776.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-09-01
AI Technical Summary
但是,纯羟丙基甲基纤维素制备的水凝胶,相变温度高、相变速率慢、力学强度低、容易发生坍塌,限制了材料的应用范围
[0015] Compared with traditional thermosensitive hydrogels, the thermosensitive composite hydrogel of this invention features a simple preparation process and exhibits characteristics such as rapid phase transition rate, non-toxicity, biodegradability, and good biocompatibility. It also possesses excellent anti-aging properties, with an adjustable LCST between 15°C and 35°C and a freezing point below -20°C. It is suitable for applications in temperature-controlled color-adjustable windows, wound dressings, and localized sustained-release drug injections.
Smart Images

Figure CN122668445A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, specifically relating to a temperature-sensitive composite hydrogel, its preparation method, and its application. Background Technology
[0002] Thermosensitive hydrogels are intelligent polymer materials capable of sensing temperature changes and undergoing reversible changes in their physical state (phase) or volume accordingly. Among them, thermochromic hydrogels are a class of thermosensitive hydrogel materials whose transparency or color changes with increasing or decreasing temperature. They can be widely used in biomedical fields such as antibacterial smart wound dressings and drug delivery carriers; in biosensing fields such as flexible sensors and wearable skin; and in intelligent engineering fields such as smart dimming windows and temperature-controlled reversible adhesives.
[0003] Hydroxypropyl methylcellulose (HPMC) is a thermosensitive polymer with a minimum critical solution temperature (LCST). Its aqueous solution is transparent and flows well below the LCST, while above the LCST it becomes highly viscous or even gel-like and opaque. Its phase transition temperature generally varies between 45°C and 90°C depending on the degree of substitution of the methyl and hydroxypropyl groups. Due to its low cost, good biocompatibility, and biodegradability, it is considered a highly promising thermotropic phase change material. However, hydrogels prepared from pure hydroxypropyl methylcellulose exhibit high phase transition temperatures, slow phase transition rates, low mechanical strength, and a tendency to collapse, limiting the material's application range.
[0004] Studies have shown (Chen Liman, Wang Tao, Li Kang. Preparation of chitosan / hydroxypropyl methylcellulose thermosensitive hydrogel [J]. Polymer Materials Science and Engineering, 2016, 32(11): 156-161.) that adding glycerol to glacial acetic acid solution of HPMC can reduce the critical phase transition temperature to 32℃ to a certain extent. However, the system relies on the acidic environment of glacial acetic acid to dissolve chitosan. Although it is neutralized to neutral by alkali, the residual trace amount of acetic acid will limit its application in acid- and alkali-sensitive wounds, cell culture, and drug sustained release scenarios. Moreover, the gelation cycle of this system is long and the in-situ molding speed is slow, making it difficult to meet the clinical needs of rapid filling and immediate shaping. Summary of the Invention
[0005] The main objective of this invention is to provide a thermosensitive hydrogel material that can undergo rapid phase transition at a specific temperature, with the phase transition temperature adjustable between 15°C and 35°C according to changes in component content, and is also bio-nontoxic and biodegradable, in order to meet the performance requirements of materials such as wound dressings, photochromic glass, and locally injectable medical gels.
[0006] To achieve the above objectives, the present invention provides a temperature-sensitive composite hydrogel, characterized in that, by mass percentage, it is composed of the following substances: 4 wt% to 8 wt% hydroxypropyl methylcellulose, 0.5 wt% to 3 wt% polylysine hydrochloride, 30 wt% to 40 wt% glycerol, and the balance being deionized water.
[0007] Preferably, the temperature-sensitive composite hydrogel as described above is characterized in that the hydroxypropyl methylcellulose should meet the following technical parameters: the viscosity of the hydroxypropyl methylcellulose aqueous solution at a concentration of 2 wt% is 3 mPa·s ~ 10 mPa·s, the mass fraction of methoxy groups is 26% ~ 33%, and the mass fraction of hydroxypropyl groups is 6.0% ~ 15%.
[0008] Preferably, the thermosensitive composite hydrogel as described above is characterized in that the polylysine hydrochloride should meet the following technical parameters: purity ≥ 95%, and the repeating unit is shown below:
[0009] In the formula, the degree of polymerization n = 25 ~ 35.
[0010] The preparation method of the above-mentioned thermosensitive composite hydrogel includes the following steps: (1) Heat the deionized water to 50℃ ~ 80℃, then mix the hydroxypropyl methylcellulose and polylysine hydrochloride evenly and add them to the deionized water, stirring until it becomes transparent; (2) Add glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) is allowed to stand at 1℃ ~ 10℃ for 5 h ~ 24 h to degas, and a thermosensitive composite hydrogel precursor is obtained; In the above preparation method, the raw materials are calculated by mass percentage as follows: hydroxypropyl methylcellulose accounts for 4 wt% to 7 wt%, polylysine hydrochloride accounts for 0.5 wt% to 3 wt%, glycerol accounts for 30 wt% to 40 wt%, and the remainder is deionized water.
[0011] In the above preparation method, the thermosensitive composite hydrogel precursor undergoes a sol-gel phase transition at 15℃ to 35℃, is in a sol state below the critical phase transition temperature, and is in a gel state above the critical phase transition temperature.
[0012] One application of the above-mentioned thermosensitive composite hydrogel is to utilize its thermosensitive phase transformation characteristics and aging resistance properties for use as a smart dimming window.
[0013] One application of the above-mentioned thermosensitive composite hydrogel is to utilize its thermosensitive phase inversion characteristics and its non-toxic, biocompatible, and biodegradable properties as a carrier for wound dressings.
[0014] One application of the above-mentioned thermosensitive composite hydrogel is to utilize its thermosensitive phase inversion characteristics and its non-toxic, biocompatible, and biodegradable properties as a sustained-release carrier for local drug injection. Beneficial effects
[0015] Compared with traditional thermosensitive hydrogels, the thermosensitive composite hydrogel of this invention features a simple preparation process and exhibits characteristics such as rapid phase transition rate, non-toxicity, biodegradability, and good biocompatibility. It also possesses excellent anti-aging properties, with an adjustable LCST between 15°C and 35°C and a freezing point below -20°C. It is suitable for applications in temperature-controlled color-adjustable windows, wound dressings, and localized sustained-release drug injections. Attached Figure Description
[0016] Appendix Figure 1 The curves showing the changes in storage modulus (G') and loss modulus (G'') of the sample prepared in Example 2 as a function of temperature; Appendix Figure 2 The curves showing the changes in storage modulus (G') and loss modulus (G'') of the sample prepared in Example 3 as a function of temperature; Appendix Figure 3 The curves showing the changes in storage modulus (G') and loss modulus (G'') of the sample prepared in Example 6 as a function of temperature; Appendix Figure 4 The transmittance of some sample examples at a wavelength of 940 nm as a function of temperature is shown. Appendix Figure 5 The images show the samples from Examples 3, 5, and 7 before and after the phase transition in a 20 mL sample vial. Detailed Implementation
[0017] This invention is not limited to the following preferred embodiments. Researchers skilled in the art can make equivalent substitutions or reasonable improvements to the formula composition, preparation process parameters, etc., based on the overall concept of this invention. All such modifications fall within the protection scope of this invention.
[0018] The performance testing, characterization analysis, and related operating procedures in each embodiment of this application are all carried out in accordance with industry-standard methods; the raw materials, experimental equipment, and environmental conditions used are all commercially available products and conventional laboratory conditions, and there is no need for special or exclusive limitations.
[0019] Hydroxypropyl methylcellulose was purchased from Aladdin Reagent Co., Ltd., with a viscosity of 6 mPa·s, methoxy content of 28%~30%, hydroxypropyl content of 7.0%~12%, and CAS number 9004-65-3. Commercially available hydroxypropyl methylcellulose from other manufacturers can achieve the technical effects of this invention.
[0020] Polylysine hydrochloride was purchased from Aladdin Reagent Co., Ltd., purity: ≥95%, CAS No.: 28211-04-3, molecular formula: [C6H 12 N2O·HCl] n The degree of polymerization is n = 25 ~ 35. Commercially available polylysine hydrochloride from other manufacturers can achieve the technical effects of this invention.
[0021] Glycerin was purchased from Bid Pharmaceutical Technology Co., Ltd., with a molecular weight of 92.09, purity of 99.90%, and CAS number 56-81-5. Commercially available polylysine hydrochloride from other manufacturers can achieve the technical effects of this invention.
[0022] All of the above raw materials are recognized as biodegradable materials.
[0023] Example 1
[0024] (1) Heat 63 g of deionized water to 50°C, then mix 4 g of hydroxypropyl methylcellulose and 1 g of polylysine hydrochloride evenly and add them to the deionized water, stirring until transparent. (2) Add 32 g of glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) was allowed to stand at 10°C for 24 h to degas, and a thermosensitive composite hydrogel precursor was obtained, labeled as P1H4G32. The pH of the obtained sample was 7.
[0025] Example 2
[0026] (1) Heat 61 g of deionized water to 50°C, then mix 6 g of hydroxypropyl methylcellulose and 1 g of polylysine hydrochloride evenly and add them to the deionized water, stirring until transparent; (2) Add 32 g of glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) was allowed to stand at 10°C for 24 h to degas, and a thermosensitive composite hydrogel precursor was obtained, labeled as P1H6G32. The pH of the obtained sample was 7.
[0027] Example 3
[0028] (1) Heat 60 g of deionized water to 80°C, then mix 7 g of hydroxypropyl methylcellulose and 1 g of polylysine hydrochloride evenly and add them to the deionized water, stirring until transparent; (2) Add 32 g of glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) was allowed to stand at 10°C for 24 h to degas, and a thermosensitive composite hydrogel precursor was obtained, labeled as P1H7G32. The pH of the obtained sample was 7.
[0029] Example 4
[0030] (1) Heat 62.5 g of deionized water to 60°C, then mix 5 g of hydroxypropyl methylcellulose and 0.5 g of polylysine hydrochloride evenly and add them to the deionized water, stirring until transparent; (2) Add 32 g of glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) was allowed to stand at 1°C for 8 h to degas, and a thermosensitive composite hydrogel precursor was obtained, labeled as P0.5H5G32. The pH of the obtained sample was 7.
[0031] Example 5
[0032] (1) Heat 60 g of deionized water to 70°C, then mix 5 g of hydroxypropyl methylcellulose and 3 g of polylysine hydrochloride evenly and add them to the deionized water, stirring until transparent; (2) Add 32 g of glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) was allowed to stand at 10°C for 5 h to degas, and a thermosensitive composite hydrogel precursor was obtained, labeled as P3H5G32. The pH of the obtained sample was 7.
[0033] Example 6
[0034] (1) Heat 62 g of deionized water to 75°C, then mix 5 g of hydroxypropyl methylcellulose and 1 g of polylysine hydrochloride evenly and add them to the deionized water, stirring until transparent. (2) Add 32 g of glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) was allowed to stand at 4°C for 24 h to degas, and a thermosensitive composite hydrogel precursor was obtained, labeled as P1H5G32. The pH of the obtained sample was 7.
[0035] Example 7
[0036] (1) Heat 54 g of deionized water to 80°C, then mix 5 g of hydroxypropyl methylcellulose and 1 g of polylysine hydrochloride evenly and add them to the deionized water, stirring until transparent. (2) Add 40 g of glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) was allowed to stand at 1°C for 24 h to degas, and a thermosensitive composite hydrogel precursor was obtained, labeled as P1H5G40. The pH of the obtained sample was 7.
[0037] Comparative Example 1 (1) Heat 95 g of deionized water to 50°C, add 5 g of weighed hydroxypropyl methylcellulose to the deionized water, and stir until transparent; (2) The liquid obtained in step (1) was allowed to stand at 10°C for 24 h to degas, and the hydrogel precursor was obtained and labeled as P0H5G0. The pH of the obtained sample was 7.
[0038] Comparative Example 2 (1) Heat 63 g of deionized water to 80°C, add 5 g of weighed hydroxypropyl methylcellulose to the deionized water, and stir until transparent; the pH of the resulting sample is 7.
[0039] (2) Add 32 g of glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) was allowed to stand at 10°C for 24 h to degas, and the hydrogel precursor was obtained and labeled as P0H5G32.
[0040] Comparative Example 3 (1) Heat 94 g of deionized water to 80°C, mix 5 g of hydroxypropyl methylcellulose and 1 g of polylysine hydrochloride evenly and add them to the deionized water, stirring until transparent. (2) The liquid obtained in step (1) was allowed to stand at 10°C for 24 h to degas, and the hydrogel precursor was obtained and labeled as P1H5G0. The pH of the obtained sample was 7.
[0041] Experiment 1: Rheological properties of composite hydrogels The rheological properties of the composite hydrogels prepared in Examples 2, 3, and 6 were tested, and the storage modulus (G') and loss modulus (G'') were measured as a function of temperature, as detailed below: The rheological properties of the composite gel were tested using a rheometer.
[0042] Test system: 20 mm flat plate.
[0043] Test conditions: the plate spacing is 1 mm, the frequency is set to 1 Hz, the temperature scan heating rate is 2 ℃ / min, and the temperature scan range is 0℃ ~ 70℃.
[0044] Test procedure: Take an appropriate amount of the prepared solution and place it between the plates. Cover the sample with a layer of dimethyl silicone oil to prevent moisture evaporation during the test. Then start the pre-set program to conduct the test.
[0045] The test results are attached. Figure 1 Appendix Figure 2 Appendix Figure 3 As shown, below 20℃, the storage modulus G' of the three samples is slightly lower than the loss modulus G'', indicating a viscous fluid state. The loss modulus G'' is small and changes gradually, while the storage modulus G' changes gradually below 14℃ and increases sharply above 14℃. At 20℃, the storage modulus G' and loss modulus G'' become equal. After 20℃, both storage modulus G' and G'' increase sharply, but storage modulus G' remains higher than loss modulus G'', indicating that the system changes from viscous to elastic after 20℃. The LCST of the three groups of samples is similar, with the modulus starting to rise sharply around 20℃. Among the final modulus strengths, P1H7G32 has the highest final storage modulus, reaching 63811 Pa; P1H6G32 is second, at 9283 Pa; and sample P1H5G32 from Example 2 has the lowest final storage modulus, at 3772 Pa. This indicates that while the thermosensitive gel phase transition mechanism remains unchanged when the hydroxypropyl methylcellulose content varies within the range of 5% to 7%, it significantly affects the final gel strength. It also shows that the composite hydrogel exhibits significant phase transition characteristics at around 20 °C.
[0046] Experiment 2: Determination of the phase transition temperature of composite hydrogels LCST is the critical temperature at which a material undergoes a phase transition (from transparent to opaque). In optical characterization, this phase transition is manifested as a sharp decrease in transmittance with increasing temperature. Therefore, on the transmittance-temperature curve, LCST corresponds to the inflection point where the curve begins to drop sharply.
[0047] Appendix Figure 4 The transmittance of the hydrogel at 940 nm is measured from 10℃ to 60℃. The samples involved include: P0H5G0, P1H5G0, P0H5G32, and P1H5G32.
[0048] The data curves for P0H5G0 show that when hydroxypropyl methylcellulose (HPMC) is present at a concentration of 5%, its LCST is 46℃. The LCST for P0H5G32 is 39℃, indicating that adding glycerol to HPMC (to a glycerol content of 32%) can lower the LCST, but the reduction is small, only 7℃. The LCST for P1H5G0 is 45℃, indicating that adding polylysine hydrochloride alone to HPMC has almost no effect on the LCST. The LCST for P1H5G32 is 25℃, indicating that adding 1% polylysine hydrochloride and 32% glycerol to 5% HPMC significantly lowers the LCST by 21℃, demonstrating a strong synergistic effect between HPMC, glycerol, and polylysine hydrochloride, resulting in a substantial reduction in LCST. This provides significant flexibility and potential for adjusting the LCST between 15℃ and 35℃.
[0049] The synergistic mechanism of hydroxypropyl methylcellulose (HPMC), polylysine hydrochloride, and glycerol on LCST is speculated as follows: (1) HPMC itself has phase transition characteristics: heating weakens the hydrogen bonds between HPMC and water, destroys the hydration layer, and the exposed hydrophobic groups cause molecular chains to aggregate under the drive of hydrophobic interactions. At the same time, inter-chain hydrogen bonds help stabilize the aggregates, thus causing a phase transition; (2) In the two-component system of polylysine hydrochloride and HPMC, the LCST of the sample changes less because the single polylysine hydrochloride component cannot destroy the hydroxypropyl methylcellulose. The hydration protective layer of cellulose is easily blocked by water molecules, so the effect on LCST regulation is weak; (3) In the three-component system of polylysine hydrochloride, HPMC and glycerol, the presence of glycerol weakens the interaction between polylysine hydrochloride and HPMC and water by competing for hydrogen bonds, and the hydration film on the molecular surface becomes thinner. On the contrary, glycerol can eliminate the spatial blockage caused by water molecules through dehydration effect, promote the hydrogen bonding and hydrophobic association between polylysine hydrochloride and HPMC, and therefore, it is easier to aggregate, and LCST is significantly reduced.
[0050] Experiment 3: Temperature-Sensitive Properties Testing of Composite Hydrogels Table 1 lists the LCST, high and low temperature optical transmittance, phase transition rate, and viscosity of each hydrogel sample, comprehensively presenting the material's temperature-sensitive response, optical control, and rheological properties, providing a basis for application selection. LCST is measured by the change in transmittance at 940 nm wavelength as a function of temperature, using a PerkinElmer Lambda1050+ UV / Vis / NIR spectrophotometer. High and low temperature optical transmittance is the transmittance of the sample at 550 nm, also measured using a PerkinElmer Lambda1050+ UV / Vis / NIR spectrophotometer. Phase transition rate is the time taken from the initial immersion of the cuvette containing the sample at 10 °C to the occurrence of a phase transition in a 70 °C water bath. Viscosity is the viscosity of the sample at 10 °C and 50 °C, measured using a Thermo Scientific HAAKE MARS 60 modular advanced rheometer.
[0051] Table 1 Temperature-sensitive performance parameters Example 1 P1H4G32 30 86.31 1.28 43 0.20 2263.07 Example 2 P1H6G32 25 80.23 0.82 39 1.74 2563.48 Example 3 P1H7G32 22 77.42 0.24 36 1.63 3294.31 Example 4 P0.5H5G32 30 83.44 1.45 42 0.18 1823.18 Example 5 P3H5G32 22 70.36 0.26 30 2.00 3588.22 Example 6 P1H5G32 25 80.23 0.87 48 0.45 2889.87 Example 7 P1H5G40 16 76.28 0.33 30 1.85 3058.21 Comparative Example 1 P0H5G0 46 88.02 81.26 119 0.11 518.23 Comparative Example 2 P0H5G32 39 87.36 8.74 100 0.13 1155.23 Comparative Example 3 P1H5G0 45 86.55 54.38 108 0.11 649.20 Table 1 shows that the LCST of the composite hydrogel of the present invention can be adjusted as needed within the range of 15℃ to 35℃ by adjusting the proportions of each component in the formulation. The LCST of the samples in the examples is significantly lower than that of the comparative example, indicating a significant synergistic effect between the polylysine hydrochloride, HPMC, and glycerol components. The phase transition temperature range of the composite hydrogel provided by the present invention is suitable for meeting the LCST requirements of temperature-sensitive hydrogels in wound dressings, thermochromic glass, and local drug injection sustained-release carriers. All sample examples exhibit good light transmittance at low temperatures, with light transmittance at 550 nm wavelength below 10% at 50℃, demonstrating good temperature-sensitive light transmittance transition characteristics and good application potential in the field of temperature-sensitive glass. The phase transition rate of the sample examples at 70℃ is significantly better than that of the comparative example. This further illustrates the significant synergistic effect of the polylysine hydrochloride, HPMC, and glycerol components, which is beneficial for applications in thermochromic windows, wound dressings, and local drug injection sustained-release. Viscosity data at 10℃ and 50℃ further demonstrate that the composite hydrogel provided by the present invention has significant temperature-sensitive properties.
[0052] Experiment 4 Cytotoxicity test of composite hydrogel As shown in Table 2, to verify the biocompatibility of the composite hydrogel of the present invention, the material was subjected to in vitro cytotoxicity testing according to the MTT colorimetric method in GB / T 16886.5-2017 "Biological evaluation of medical devices - Part 5: In vitro cytotoxicity test".
[0053] Table 2 Cytotoxicity (MTT assay) Example 1 It was not cytotoxic, and the survival rate of the test sample extract (100%) was 93.40%, with the survival rate of all test sample administration groups being higher than 70%. Example 2 It was not cytotoxic, and the survival rate of the test sample extract (100%) was 90.80%, with the survival rate of all test sample administration groups exceeding 70%. Example 3 It was not cytotoxic, and the survival rate of the test sample extract (100%) was 91.22%, with the survival rate of all test sample administration groups exceeding 70%. Example 4 It was non-cytotoxic, with a survival rate of 95.92% for the test sample extract (100%), and the survival rate of all test sample administration groups was higher than 70%. Example 5 It was not cytotoxic, and the survival rate of the test sample extract (100%) was 85.92%, with the survival rate of all test sample administration groups exceeding 70%. Example 6 It was non-cytotoxic, with a survival rate of 90.34% in the test sample extract (100%), and the survival rate of all test sample administration groups was higher than 70%. Example 7 It was not cytotoxic, and the survival rate of the test sample extract (100%) was 93.19%, with the survival rate of all test sample administration groups exceeding 70%. Comparative Example 1 It was non-cytotoxic, with a survival rate of 93.53% in the test sample extract (100%), and the survival rate of all test sample administration groups was higher than 70%. Comparative Example 2 It was not cytotoxic, and the survival rate of the test sample extract (100%) was 93.01%, with the survival rate of all test sample administration groups exceeding 70%. Comparative Example 3 It was not cytotoxic, and the survival rate of the test sample extract (100%) was 89.42%, with the survival rate of all test sample administration groups exceeding 70%. The cell compatibility of the material was evaluated by measuring the relative cell proliferation rate. The results showed that the composite hydrogel had no obvious cytotoxicity and good biosafety performance, meeting the biosafety requirements of wound dressings and local drug injection sustained-release carriers.
[0054] Experiment 5: UV aging resistance of composite hydrogels As shown in Table 3, to evaluate the stability of the composite hydrogel in this system under long-term irradiation under 340 nm long-wave ultraviolet light, the hydrogel samples were continuously irradiated using a UVA-340 fluorescence ultraviolet aging test chamber for 1 day and 60 days of cumulative irradiation, respectively, and the optical transmittance was tested simultaneously at 10℃ and 40℃. 550 nm is in the visible green light band and is the characteristic wavelength with the strongest visual response of the human eye. The transmittance performance at this wavelength can directly characterize the visible light transmittance effect of the hydrogel as a light-transmitting substrate. Therefore, this wavelength was selected in this experiment to record the transmittance changes of samples at 550 nm under different aging times and temperatures.
[0055] Table 3 Performance degradation data under UV exposure Example 1 83.48 5.23 80.16 5.14 Example 2 83.16 4.21 82.95 4.04 Example 3 84.22 3.82 82.51 3.02 Example 4 83.14 15.82 82.95 16.24 Example 5 75.23 0.82 72.56 0.24 Example 6 78.12 9.34 75.19 8.55 Example 7 77.25 3.54 76.29 3.11 Comparative Example 1 87.54 88.42 80.15 79.26 Comparative Example 2 85.91 86.77 79.08 80.14 Comparative Example 3 86.21 86.93 80.25 78.25 The data in Table 3 show that the composite hydrogel provided by the present invention still exhibits good temperature-sensitive phase transition characteristics after long-term UV aging, and the overall performance of the composite hydrogel has not changed significantly, indicating that the composite hydrogel provided by the present invention has good UV aging resistance.
[0056] Experiment 6: Freezing point temperature test of composite hydrogels At low temperatures, ice crystals easily precipitate inside hydrogels, damaging the internal cross-linked network structure and causing them to lose their original optical and mechanical properties. The freezing point is the core indicator for evaluating the low-temperature tolerance of hydrogels. Each group of samples was placed in a programmed low-temperature test chamber for uniform gradient cooling. The critical temperature at which visible ice crystals appeared inside the sample and the system solidified was observed in real time. This temperature is the freezing point of the sample. The test results for each group are summarized in Table 4.
[0057] Table 4 Comparison of freezing point temperatures of composite hydrogels Example 1 P1H4G32 -25 Example 2 P1H6G32 -25 Example 3 P1H7G32 -24 Example 4 P0.5H5G32 -25 Example 5 P3H5G32 -23 Example 6 P1H5G32 -25 Example 7 P1H5G40 -30 Comparative Example 1 P0H5G0 0 Comparative Example 2 P0H5G32 -25 Comparative Example 3 P1H5G0 -1 The data in Table 4 show that the composite hydrogel provided by this invention has a freezing point below -20°C, which is beneficial for this type of composite hydrogel to be used as a key material for temperature-adjustable windows.
[0058] Experiment 7: Physical Observation Experiment of Phase Transition The composite thermosensitive hydrogels prepared in Examples 3, 5, and 7 were placed in 20 mL screw-top sample vials, and the thermosensitive phase transition behavior of the systems was observed sequentially at -20℃, 10℃, 30℃, and 50℃. The corresponding observation results are attached. Figure 5 As shown in the figure. Observation results show that the system is a clear liquid at -20℃, with a transparent bottle and a clearly identifiable background behind it. When the temperature is raised to 10℃, the composite hydrogel still maintains high transparency, and the background outline behind the bottle is clear. When the temperature rises to 30℃, the transparency of the composite hydrogel decreases significantly, and the background outline behind the bottle becomes blurred. When the temperature is further raised to 50℃, the light transmittance of the system further decreases, and the degree of turbidity increases significantly. The above phenomena prove that the composite hydrogel of the present invention can undergo a reversible temperature-sensitive phase transition in the near-room temperature range, possessing excellent temperature-sensitive dimming characteristics, and has broad application prospects in the field of intelligent temperature-controlled dimming windows.
Claims
1. A temperature-sensitive composite hydrogel, characterized in that, It consists of the following substances by mass percentage: 4 wt% to 8 wt% hydroxypropyl methylcellulose, 0.5 wt% to 3 wt% polylysine hydrochloride, 30 wt% to 40 wt% glycerol, and the balance being deionized water.
2. The thermosensitive composite hydrogel according to claim 1, characterized in that, The hydroxypropyl methylcellulose shall meet the following technical parameters: the viscosity of the aqueous solution of hydroxypropyl methylcellulose at a concentration of 2 wt% is 3~10 mPa·s, the mass fraction of methoxy group is 26%~33%, and the mass fraction of hydroxypropyl group is 6.0%~15%.
3. The thermosensitive composite hydrogel according to claim 1, characterized in that, The polylysine hydrochloride should meet the following technical parameters: purity ≥ 95%, and the repeating unit is shown below: , In the formula, the degree of polymerization n = 25 ~ 35.
4. A method for preparing a thermosensitive composite hydrogel according to claims 1 to 3, characterized in that, Includes the following steps: (1) Heat deionized water to 50 ℃ ~ 80 ℃, then mix hydroxypropyl methylcellulose and polylysine hydrochloride evenly and add it to the deionized water, stirring until transparent; (2) Add glycerol to the solution prepared in step (1) and stir to mix evenly; (3) The liquid obtained in step (2) is allowed to stand at 1 ℃ ~ 10 ℃ for 5 h ~ 24 h to degas, and a thermosensitive composite hydrogel precursor is obtained; The raw materials, calculated by mass percentage, consist of hydroxypropyl methylcellulose at 4 wt% to 7 wt%, polylysine hydrochloride at 0.5 wt% to 3 wt%, glycerol at 30 wt% to 40 wt%, and the remainder being deionized water.
5. An application of the thermosensitive composite hydrogel according to claims 1 to 4, utilizing its thermosensitive phase transformation characteristics and aging resistance characteristics, for use as a smart dimming window.
6. An application of the thermosensitive composite hydrogel according to claims 1 to 4, utilizing its thermosensitive phase inversion characteristics and its non-toxic, biocompatible, and biodegradable properties, as a carrier for wound dressings.
7. The use of the thermosensitive composite hydrogel according to claims 1 to 4, utilizing its thermosensitive phase inversion characteristics and its non-toxic, biocompatible and biodegradable properties, as a sustained-release carrier for local drug injection.